Estimation of Carbon Stocks in Green Open Spaces (RTH) in East Pagutan, Mataram City - Nufus, Husniatun; Markum, Markum; Ningsih, Rima Vera (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The impact of global warming has made climate change a major area of ​​concern in the modern era. This phenomenon is caused by the increasing concentration of gases known as greenhouse gases (GHGs), which include carbon dioxide (CO2), methane (CH4), and nitrous oxide (N₂O). These gases increase the amount of heat trapped in the Earth's atmosphere, some of which is absorbed and some of which is reflected back to Earth. Analyzing the capacity of Pagutan Timur Green Open Space for carbon storage and carbon dioxide absorption in Mataram City is the aim of this study. Purposive and census methodologies were used in this study, which was conducted in Pagutan Timur Green Open Space, Mataram City. Qualitative and quantitative data analysis were used. The results of the study found that a total of 299.99 tons of carbon were stored, 638.27 tons of biomass were stored, and 1,100.95 tons of carbon were absorbed. This means that the total area is 8.2 hectares, or 36.49 tons of carbon stored per hectare. The conclusion is that Pagutan Timur Green Open Space can store carbon and absorb carbon dioxide in Mataram City.